1983
DOI: 10.1128/jcm.18.1.40-42.1983
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of calibrated-loop transfer

Abstract: The accuracy of the 0.001-ml calibrated platinum loop was tested by two methods: visible absorption spectroscopy and weight determinations. By both methods it was demonstrated that the volume of the loop delivery is related to the angle at which the loop is withdrawn from the solution being sampled and the diameter of the container, provided that the volume in the container is adequate to cover the loop. Vertical sampling from small-diameter containers (less than or equal to 7-mm inside diameter) delivered app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Apart from the performance characteristics linked to the calibration of the loop, many other variables may cause sampling errors. Less fluid is sampled when containers with small diameters are used, and a larger volume is sampled when the loop is inserted and withdrawn at a 45°angle or when the shank of the loop is immersed (1,2). Containers with small diameters may cause the loop to pick up a smaller volume since plastic-liquid (adhesive) forces are greater than liquid-liquid (cohesive) forces (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the performance characteristics linked to the calibration of the loop, many other variables may cause sampling errors. Less fluid is sampled when containers with small diameters are used, and a larger volume is sampled when the loop is inserted and withdrawn at a 45°angle or when the shank of the loop is immersed (1,2). Containers with small diameters may cause the loop to pick up a smaller volume since plastic-liquid (adhesive) forces are greater than liquid-liquid (cohesive) forces (1).…”
Section: Discussionmentioning
confidence: 99%
“…Less fluid is sampled when containers with small diameters are used, and a larger volume is sampled when the loop is inserted and withdrawn at a 45°angle or when the shank of the loop is immersed (1,2). Containers with small diameters may cause the loop to pick up a smaller volume since plastic-liquid (adhesive) forces are greater than liquid-liquid (cohesive) forces (1). When the shank of the loop is wetted by deep immersion into the fluid, excess liquid drains down and enlarges the volume transferred (2).…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for decreased specificities by the test methods is that low-level bacteriuria may not be detected by the culture method. Also, it has been reported that the culture method may have an error rate of as high as 50% (1). Another contributing factor may have been the presence of antimicrobial agents which inhibit microbial growth but do not inhibit detection by bioluminescence or filtration (6).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have indicated that the use of calibrated loops can be imprecise ( 3 ). Albers and Fletcher ( 8 ) noted that “the use of the calibrated loop by clinical microbiologists to determine colony counts from urine specimens is only semiquantitative and not very reliable, as the reproducibility of the method is dependent on many uncontrolled variables.” In an evaluation of the WASP instrument, Harrington and colleagues ( 9 ) noted that the colony counts produced by the WASP increased as the loops were inserted deeper into the specimen tube. This was most notable in this study with the WASP 1-μl loop.…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that the relatively higher colony counts obtained with the WASP-1 and WASP-10 instruments compared to those with a calibrated pipette were due to the use of a wire loop to transfer the specimen from the transport tube to the agar plate. As noted by Albers and Fletcher ( 8 ), there are inherent inaccuracies associated with the use of a 1-μl loop. Importantly, the InoqulA and WASP instruments utilize different technologies to determine the depth of the liquid to which the transfer device (pipette versus loop) goes.…”
Section: Discussionmentioning
confidence: 99%